2017
DOI: 10.5009/gnl17033
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Prognosis of Diffuse-Type Early Gastric Cancer Diagnosed during Health Check-Ups

Abstract: Background/AimsBecause of the poor prognosis of diffuse-type gastric cancer, early detection is important. We investigated the clinical characteristics and prognosis of diffuse-type early gastric cancer (EGC) diagnosed in subjects during health check-ups.MethodsAmong 121,111 subjects who underwent gastroscopy during a routine health check-up, we identified 282 patients with 286 EGC lesions and reviewed their clinical and tumor-specific parameters.ResultsPatients with diffuse-type EGC were younger, and 48.1% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 32 publications
5
25
0
2
Order By: Relevance
“…The baseline age at H. pylori eradication was less in patients with mild or moderate than with severe gastric atrophy in our cohort, but the risk did not change in case of intestinal-type cancer through the follow-up period up to 21 years regardless of the grade of baseline mucosal atrophy, a finding suggesting that factors other than aging are involved. Early gastric cancers of diffuse type are often superficial and flat, with only discoloration and are difficult to recognize endoscopically [23]. During the past decades, endoscopy equipment has improved greatly, and techniques such as magnifying endoscopy with narrow band imaging have improved the ability to detect early diffuse-type gastric cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…The baseline age at H. pylori eradication was less in patients with mild or moderate than with severe gastric atrophy in our cohort, but the risk did not change in case of intestinal-type cancer through the follow-up period up to 21 years regardless of the grade of baseline mucosal atrophy, a finding suggesting that factors other than aging are involved. Early gastric cancers of diffuse type are often superficial and flat, with only discoloration and are difficult to recognize endoscopically [23]. During the past decades, endoscopy equipment has improved greatly, and techniques such as magnifying endoscopy with narrow band imaging have improved the ability to detect early diffuse-type gastric cancer [24].…”
Section: Discussionmentioning
confidence: 99%
“…The calibration range of this immunoassay is 0.4–8.0 U/mL, with the Hp-IgG titer classified as follows: negative, 0–1.0 U/mL; positive, 1.1–7.9 U/mL; and high positive, ≥8.0 U/mL. We divided the patients in the H. pylori-positive group into two approximately equal subgroups according to a cutoff value chosen to ensure the same number of cases for each subgroup: the low-positive group (1.1–4.2 U/mL, n = 288) and the mid-positive group (4.3–7.9 U/mL, n = 290) ( Fig 1 )[ 9 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…pylori infection status, with the proportion of diffuse-type GC being higher in patients with current infection than in those with past infection [ 8 ]. In addition, several studies including our previous study have suggested that subjects with a low Hp-IgG titer are at high risk for intestinal-type GC, whereas those with a high Hp-IgG titer are at increased risk for diffuse-type GC [ 9 12 ]. Chronological change in Hp-IgG titers which decrease with the progression of gastric mucosal atrophy may be attributable to the association between past infection or low Hp-IgG titer and intestinal-type GC [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, mixed‐type EGC can be simply classified as predominantly differentiated (MD) or predominantly undifferentiated (MU) types. Various studies have investigated the risk of LNM in these two types of EGC . Mita and Shimoda compared the clinicopathological features of submucosal differentiated EGC with and without LNM, and found that the rate of LNM in mixed EGC was higher, which was further identified in the multivariate analysis .…”
Section: Endoscopic Resection Indications For Egcmentioning
confidence: 99%